A study on growth, optical, mechanical, and NLO properties of 2-Mercaptobenzimidazole, 2-Phenylbenzimidazole and 2-Hydroxy benzimidazole single crystals: a comparative investigation. (12th May 2017) - Muthuraja, A.; Kalainathan, S.
Abstract: 2-Mercaptobenzimidazole (2MBMZ), 2-Phenly benzimidazole (2PBMZ), 2-Hydroxy Benzimidazole (2HBMZ), single crystals were successfully grown by slow evaporation solution growth technique. The grown crystals were subjected to single crystal X-ray diffraction, UV–vis NIR, chemical etching, Vickers microhardness analysis, Laser damage theroshold and Z-scan analysis; all the results were compared. Single crystal X-ray diffraction confirmed the lattice parameters of the grown crystals. The range and the percentage of the optical transmission are ascertained by UV–vis spectrum. The structure of the grown crystals was further confirmed using FT-NMR analysis. The refractive index of the 2-MBMZ, 2-PBMZ, and 2-HBMZ grown crystals were measured and found to be 1.653, 1.652, and 1.623, respectively. The chemical etching studies were carried out to assess the perfection of the grown crystals. The mechanical stability of the grown crystals was identified from Vickers microhardness analysis. The 2-PBMZ possesses higher mechanical stability than the 2-HBMZ and 2-MBMZ crystals. The third-order non-linear optical properties like non-linear absorption coefficient ( β ), non-linear refractive index ( n 2 ), and susceptibility ( χ 3 ) of grown crystals were studied using the Z-scan technique. The 2-MBMZ and 2-HBMZ ( χ 3 ) value found to be in the range of 2.60182 × 10 −5 esu, and 1.87049 × 10 −5 esu, respectively. 2-PBMZ crystal owns higher laser damage threshold value than the 2-MBMZ and 2-HBMZ grown crystals.